Rancang Bangun Prototipe Home Automation Menggunakan Teknologi Internet Of Things - Syahban Rangkuti; Eliyana Firmansyah; Andrie Mochammad Yadi (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Internet of Things (IoT) technology is often used to monitor and control electronic equipment remotely using the internet. The implementation of Internet of Things technology can be applied to home automation. The implementation of IoT in a home automation system (home automation) can be used to control home lights, home temperature, and electronic plates in the home, and it can even be used to determine the whereabouts of home occupants. In this research, we will create a home automation prototype with the Internet of Things concept, which can be built using the NodeMCU module integrated with a web application. The data communication system in home automation will communicate with the MQTT server and can send data (publish) and receive data (subscribe). The home automation system can carry out manual or scheduled monitoring and control. It can provide notifications whenever a change in the condition or status of the device is being monitored or controlled. Changes in conditions can also occur through sensor readings connected to the NodeMCU module.